Malaysian road traffic crash data: Where do we stand now - Ahmad Noor Syukri, Zainal Abidin; Azzuhana, Roslan; Roziana, Shahril; Arief Hakimi, Azmi; Ahmad Shahir, Jamaludin; Nur Aini Safiah, Abdullah; Zulhaidi, Mohd Jawi; Khairil Anwar, Abu Kassim (Penerbit UMP, 2021)
Statistically around the world, the number of people killed on the roads are approximately 1.3 million. A road traffic crash is not only a global pandemic that kills more than a million people per year but has also become a major public health concern in most countries, including Malaysia. With consistent standardized collection and management of data, these data will provide beneficial and accurate insight for trends monitoring future time series prediction and ultimately, reliable review of currently implemented programmes. In Malaysia, the Royal Malaysian Police (RMP) involves primarily of collecting road crash data, along with the routine traffic management and enforcement activities. To complement that, Malaysia is amongst the very few countries in ASEAN which possess its own research-based road crash investigations. This is as the effort in evidence-based approach to tackle road safety issues. Inputs from the in-depth research-based investigation are reported to policymakers and relevant authorities/industries which significantly assist in the development of safety countermeasures. To manage the data is a challenging task especially when it involves multiple agencies with different focuses, requirements and countless bureaucracies. Nevertheless, future understanding and potential efforts in consolidating these data pools will further enhance the national crash database as well as open new dimensions of the Malaysian crash database.